IsoQC (QPCTL) knock-out mice suggest differential substrate conversion by glutaminyl cyclase isoenzymes - Becker, Andreas; Eichentopf, Rico; Sedlmeier, Reinhard; Waniek, Alexander; Cynis, Holger; Koch, Birgit; Stephan, Anett; Baeuscher, Christoph; Kohlmann, Stephanie; Hoffmann, Torsten; Kehlen, Astrid; Berg, Sabine; et al. (Biological Chemistry, 2016)
Secretory peptides and proteins are frequently modified by pyroglutamic acid (pE, pGlu) at their N-terminus. This modification is catalyzed by the glutaminyl cyclases QC and isoQC. Here, we decipher the roles of the isoenzymes by characterization of IsoQC-/- mice. These mice show a significant reduction of glutaminyl cyclase activity in brain and peripheral tissue, suggesting ubiquitous expression of the isoQC enzyme. An assay of substrate conversion in vivo reveals impaired generation of the pGlu-modified C-C chemokine ligand 2 (CCL2, MCP-1) in isoQC-/- mice. The pGlu-formation was also impaired in primary neurons, which express significant levels of QC. Interestingly, however, the formation of the neuropeptide hormone thyrotropin-releasing hormone (TRH), assessed by immunohistochemistry and hormonal analysis of hypothalamic-pituitary-thyroid axis, was not affected in isoQC-/-, which contrasts to QC-/-. Thus, the results reveal differential functions of isoQC and QC in the formation of the pGlu-peptides CCL2 and TRH. Substrates requiring extensive prohormone processing in secretory granules, such as TRH, are primarily converted by QC. In contrast, protein substrates such as CCL2 appear to be primarily converted by isoQC. The results provide a new example, how subtle differences in subcellular localization of enzymes and substrate precursor maturation might influence pGlu-product formation.
EVALuna2:24978